Landfill leachate treatment using subsurface flow constructed wetlands enhanced with magnetic field - Rasit, Nazaitulshila (2006)
Leachate is a complex and highly polluted wastewater. Constructed wetlands are potentially good, low-cost and appropriate technological treatment systems for treating leachate. Thus, the purpose of this study was to assess the impact of magnetic field towards the performance of vertical and horizontal subsurface flow constructed wetland (SSF) vegetated with Limnocharis flava for leachate treatment. The metals uptake by plants also been investigated. The main parameters evaluation are total suspended solid (TSS), turbidity, ammoniacal nitrogen (NH4 -N), nitrate (NO3 -N), phosphorus and metals (ferum and manganese). Experiments were run in two systems, which were vertical SSF and horizontal SSF, conducted in duration of 18 days for each. Each of the system consists of control, vegetated and vegetated with magnet tanks. Results show that the capability of emergent plant in the removal of all parameters did show a performance compared to unplanted control. Presence of the vegetation did show there were a substantial removal shown for NH4 -N>80%, NO3 -N>70% and heavy metals (Fe>96 and Mn>83%). However, the capability of emergent plant has lower removal efficiency in TSS (<48%). Constructed wetland with magnetic field had a greater ability than vegetated treatment in removal of TSS and metals. For those parameters, highest removal was recorded in both systems compared to other treatment which was >86% for TSS, complete removal for Fe and for Mn, removal was >88%. The effect of different flow format used in this study had shown that vertical flow format do provide a good condition for nitrification but no denitrification. On the other hand, horizontal flow format cannot provide nitrification because of their limited oxygen transfer capacity. The treatability of vertical SSF had showed greater removal in NH4 -N (>87%) and Mn (>78%) while horizontal flow had showed greater removal of NO3 -N (>66%). Others parameters did not contribute to substantial differences between vertical and horizontal SSF constructed wetlands. The result for metals uptake by Limnocharis flava shows that the plants leaves and roots are capable to absorb Fe and Mn in leachate